What can philosophers learn from psychopathy? - Maibom, Heidi (Array, 2018)
Many spectacular claims about psychopaths are circulated. This contribution aims at providing the reader with the more complex reality of the phenomenon (or phenomena), and to point to issues of particular interest to philosophers working in moral psychology and moral theory. I first discuss the current evidence regarding psychopaths’ deficient empathy and decision-making skills. I then explore what difference it makes to our thinking whether we regard their deficit dimensionally (as involving abilities that are on or off) and whether we focus on primary or secondary psychopathy. My conclusion is that most grand claims about psychopathy settling long-standing debates in moral philosophy and psychology are overblown, but there is much to be learnt from this disorder when it comes to formulating modern theories of moral psychology.